social systems theory /Julia M. Norlin,...[et al.] - Norlin, Julia M (Boston, 2003)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Human behavior; Social service; Social systems -- Mathematical models; Hành vi con người; Dịch vụ xã hội; Hệ thống xã hội -- Mô hình toán học